Canvas of culture: public art’s role in reinvigorating Pekan Parit - Muhamad Ferdhaus Sazali; Nur Ayunni Che Ahmad; Hasnizam Ab’dul Hamid; Mohamad Azal Fikri Ali (Penerbit Universiti Kebangsaan Malaysia, 2024)
Public art is instrumental in enhancing tourism in Pekan Parit, Perak, by enriching the area cultural landscape. This study explores the multifaceted influence of public art on community perceptions, emotional responses, and its potential to attract tourists. We employed a mixed-methods design to collect data from 103 respondents through surveys, evaluating community attitudes towards public art and its role in fostering a cohesive community and boosting tourism. Key findings reveal that public art not only enhances Pekan Parit’s aesthetic appeal but also significantly influences both residents and visitors. However, community engagement is closely linked to the effectiveness of public art in attracting tourists, so artistic initiatives must resonate with both locals and tourists. This underscores the critical role of public art in reflecting and preserving the town's cultural identity while involving the community in the planning and execution of these projects. The research concludes that public art can be a powerful catalyst for sustainable tourism growth, facilitating deeper connections to the area’s cultural heritage and enhancing the overall visitor experience. These insights are essential for policymakers, urban planners, and cultural practitioners seeking to leverage public art as a strategic tool for revitalising tourism in Pekan Parit, Perak.